Lynx lynx subsp. isabellinus Blyth 1847 - Wilson, Don E.; Reeder, DeeAnn (The Johns Hopkins University Press, 2005)
Lynx lynx subsp. isabellinus Blyth 1847 Synonyms: Lynx lynx subsp. kamensis (Satunin 1905); Lynx lynx subsp. tibetanus (Gray 1863); Lynx lynx subsp. wardi (Lydekker 1904). Published as part of Wilson, Don E. & Reeder, DeeAnn, 2005, Order Carnivora, pp. 532-628 in Mammal Species of the World: a Taxonomic and Geographic Reference (3 rd Edition), Volume 1, Baltimore :The Johns Hopkins University Press on page 541, DOI: 10.5281/zenodo.7316519